Pure submodules of BCK-modules - N. Motahari; T. Roudbari Lor (Journal of Hyperstructures)
In this paper by considering the notion of BCK-module, we introduce pure BCK- submodules and we prove some results by it. In particular, we show that if X is a BCK- algebra, M is a cyclic BCK-module and N a prime BCK- submodule of M, then N is a pure BCK-submodule of M.